EFFECT OF 30° HEAD-UP POSITION ON INTRACRANIAL PRESSURE CHANGE IN PATIENTS WITH HEAD INJURY IN SURGICAL WARD OF GENERAL HOSPITAL OF Dr. R. SOEDARSONO PASURUAN - Pertami, Sumirah Budi; Sulastyawati, Sulastyawati; Anami, Puthut (YCAB Publisher & IAKMI SULTRA, 2017)
Background: Head-injured patients have traditionally been maintained in the head-up position to ameliorate the effects of increased intracranial pressure (ICP). However, it has been reported that the 15 degrees head-up position may improve cerebral perfusion pressure (CPP) and outcome. We sought to determine the impact of 30 and 15 degrees on intracranial pressure change.Methods: This was a quasi-experimental study with posttest only control time series time design. There were 30 head-injured patients was selected using consecutive sampling, with 15 assigned in the treatment (30° head-up position) and control group (15° head-up position). Intracranial pressure variable was identified using the level of consciousness and mean arterial pressure parameters. Wilcoxon signed rank test was used for data analysisResults: Findings showed p-value 0.010 (<0.05) on awareness level and p-value 0.031 (<0.05) on mean arterial pressure, which indicated that there was a statistically significant effect of the 30° head-up position on level of awareness and mean arterial pressure.Conclusion: There was a significant effect of the 30° head-up position on intracranial pressure changes, particularly in the level of awareness and mean arterial pressure in patients with head injury. It is recommended that for health workers to provide knowledge regarding this intervention to prevent increased intracranial pressure.